2004
DOI: 10.1038/sj.jp.7211102
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance Pulse Oximetry from Core Body in Neonates and Infants: Comparison to Arterial Blood Oxygen Saturation and to Transmission Pulse Oximetry

Abstract: OBJECTIVE:To compare pulse oximetry oxygen saturation (SpO 2 ) measured by a novel reflectance method from core body to arterial oxygen saturation (SaO 2 ) in neonates and infants. Transmission pulse oximetry (TPO) was measured for comparison. STUDY DESIGN:We monitored 18 infants by the two pulse oximeters simultaneously. The reflectance pulse oximetry (RPO) (PRO2, ConMed, Utica, NY) was measured on the upper back or chest, while the TPO (N395-Nellcor, Pleasanton, CA) was measured from the finger of the infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The extremely low values of SpO 2 may have been artificially low due to inherent measurement properties of pulse oximetry. The accuracy of this technique can be diminished when saturation is less than 85% [29] and in situations of low tissue blood perfusion [30]. In addition, Yamaya et al [31] reported that, in conditions of hypoxia and severe reductions of pH, further decrements in measured O 2 saturation may occur even in the absence of any true changes in pO 2 .…”
Section: Respiratory Rate Carbon Dioxide and Oxygenmentioning
confidence: 97%
“…The extremely low values of SpO 2 may have been artificially low due to inherent measurement properties of pulse oximetry. The accuracy of this technique can be diminished when saturation is less than 85% [29] and in situations of low tissue blood perfusion [30]. In addition, Yamaya et al [31] reported that, in conditions of hypoxia and severe reductions of pH, further decrements in measured O 2 saturation may occur even in the absence of any true changes in pO 2 .…”
Section: Respiratory Rate Carbon Dioxide and Oxygenmentioning
confidence: 97%
“…With no obstruction offered by any bony material, it is theorised that the AF can be used as an optical window where both red and infrared light can be used to make PPG measurements at a point below the scalp to directly monitor saturation. Other studies into SpO 2 readings from the core of the neonate would also support this [6].…”
Section: Introductionmentioning
confidence: 76%
“…7 The fifth vital sign for assessing every newborn is the Pulse oximeter oxygen saturation (SpO 2 ). 8 Normally the saturation of oxygen is 93% in healthy newborns in room air and differs according to post-natal age. 9 The adequacy of oxygenation and ventilation are assessed by the Arterial blood gas analysis which is the gold standard.…”
Section: Discussionmentioning
confidence: 99%